2016
DOI: 10.1080/15592294.2016.1146854
|View full text |Cite
|
Sign up to set email alerts
|

Methylation and expression analyses of Pallister-Killian syndrome reveal partial dosage compensation of tetrasomy 12p and hypomethylation of gene-poor regions on 12p

Abstract: To ascertain the epigenomic features, i.e., the methylation, non-coding RNA, and gene expression patterns, associated with gain of i(12p) in Pallister-Killian syndrome (PKS), we investigated single cell clones, harboring either disomy 12 or tetrasomy 12p, from a patient with PKS. The i(12p)-positive cells displayed a characteristic expression and methylation signature. Of all the genes on 12p, 13% were overexpressed, including the ATN1, COPS7A, and NECAP1 genes in 12p13.31, a region previously implicated in PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The results of the current study demonstrated that miR-875-5p served as an oncogene in BCa. COPS7A belongs to the COP9 signalosome complex (CSN) complex ( 28 ). CSN expression has been shown to control cell cycle progression and to be associated with carcinogenesis ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study demonstrated that miR-875-5p served as an oncogene in BCa. COPS7A belongs to the COP9 signalosome complex (CSN) complex ( 28 ). CSN expression has been shown to control cell cycle progression and to be associated with carcinogenesis ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously identified altered methylation patterns in cases with genomic gains, such as hypomethylation of gene-poor regions on the trisomic/tetrasomic chromosomes in HeH, on chromosomes 7 and 14 in colon cancer with trisomies of these chromosomes, on chromosome 8 in constitutional trisomy 8 mosaicism, and on 12p in Pallister–Killian syndrome with gain of i(12p)[ 50 54 ]. We hence hypothesized that also gain of 1q might be associated with such methylation changes and ascertained the methylation status of cancer tissue-specific differentially methylated regions, promoters, CpG islands, shores, and shelves on 1q.…”
Section: Discussionmentioning
confidence: 99%
“…2a). Next, to confirm chimerism, we analyzed the B-allele frequency of autosomes and the X chromosome [13,14]. We found both a region showing five allele combinations, where possible SNP genotypes were BB-BB, BB-BA, BB-AA, BA-AA, and AA-AA, which means that there were three or four chromosome sets, and a region showing three allele combinations, where the possible SNP genotypes were BB-BB, AB-AB, and AA-AA, which means that there were two identical chromosome sets in the autosomes (Fig.…”
mentioning
confidence: 99%